Study on the application effect of CDIO-based training mode in ECMO training for ICU nurses - Zhu, Rui; Geng, Yufang; Wei, Yang; Liu, Nian; Li, Jingjing; Shao, Min (Vojnosanitetski pregled, 2025)
Background/Aim. Nurses in the intensive care unit (ICU) must have strong professional skills due to excessive workloads, high nursing risk events, and frequent nurse-patient disagreements. The aim of the study was to examine the use of Conceive, Design, Implement, and Operate (CDIO)-based teaching modalities in ICU nurses’ extracorporeal membrane oxygenation (ECMO) training and find ways to increase training quality and professional capabilities. Methods. This study included 60 nurses and 100 ICU patients, selected from January 2020 to December 2021. They were split into an observation group (OG) and a control group (CG) (30 nurses and 50 patients each) based on ECMO nurse training methods. OG used CDIO-based training, whereas CG used ordinary training. Nurses’ theoretical knowledge, fundamental nursing skills, professional nursing skills, Competency Inventory for Registered Nurses (CIRN) score, Critical Thinking Disposition Inventory-Chinese Version (CTDI-CV) score, and self-efficacy (General Self-Efficacy Scale – GSES) score were assessed. Results. Nurses’ theoretical knowledge, basic skills, and professional skills were significantly greater (p < 0.05) in OG (95.34 ± 1.97, 56.84 ± 1.97, 36.19 ± 2.04) than in CG (87.11 ± 2.82, 51.17 ± 2.42, 31.52 ± 2.38). After training, nurses in OG had higher combined scores in CIRN, CTDI-CV, and GSES (75.84 ± 9.59) compared to CG (67.35 ± 8.43, p < 0.05). Conclusion. ICU nurses’ ECMO training benefits from CDIO-based modalities. It may considerably increase nurses’ evaluation outcomes, core competency, critical thinking, self-efficacy, and self-learning. Training quality is far greater than traditional training, making it worthy of promotion and utilization.